MINIPRINT ARTWORK CREATION WITH SATO KEWAN OBJECT - Adi, S.Sn, M.Sn, Sigit Purnomo; Mohamed Saat, Mohammad Khizal; Tri Marutama, I Gusti Ngurah (ARTISTIC : International Journal of Creation and Innovation, 2021)
Animals have provided humans with everything from meat to eggs to pleasure. Thus, animals, including chameleons, must be rescued from extinction. The chameleon's uniqueness makes it an intriguing subject for artistic creation. The purpose of this artwork is to visualize the concept of personal expression through miniprint works using Sato Kewan (variety of animals) object, specifically the chameleon. The creation of this printmaking work is part of artistic research, more specifically research into art practice, which is conducted using plywood as a medium, an abstract expressionism style, and the concept of art as personal expression. The stages of creation include experimentation, contemplation, and formation. A chameleon miniprint reflecting personal expression is created as a result of the creation process. Hence, visualization of chameleon miniprints using advanced printing techniques can result in abstract expressionism-inspired printmaking works. The creation, which incorporates traditional and contemporary art elements, is expected to be competitive nationally and internationally.